Labour Force Composition and Labour Shortage in North-Western Romania: A Cross-County Comparison - FÖLDES, Ionuț; MIHÁLY, Zoltán; POP, Cristian (Studia Universitatis Babeș-Bolyai Sociologia, 2024)
The paper analyses the labour force composition of two adjacent counties in north-west Romania: Maramureș and Sălaj. Regionally, employers stress the lack of available labour force and resort to commuter networks from nearby rural areas and immigrant labour. Why labour shortage? It is argued that Romania’s FDI-reliant export-led growth model factors in. Namely, the growth model’s reliance on low-cost labour that reduces employment incentives to a minimum (often minimum wage) and employment in repetitive labour-intensive activities make the prospect less attractive. If technological upgrading – requiring skilled employees – is absent, regional labour availability tends to be an issue. Alternative subsistence methods are favoured: seasonal transnational migration, household agricultural subsistence and remittances from relatives. Tying livelihood to families and households, these methods pool resources to replace (even if in part) wage labour under global market-dependency conditions.